ANALISIS STRUKTUR KEPEMILIKAN TERHADAP DISCRETIOARY ACCRUAL THE ANALYSIS OF OWNERSHIP STRUCTURE ON DISCRETIONARY ACCRUAL - jatiningrum, citrawati (Jurnal Manajemen dan Keuangan, 2011)
This study aims to empirically prove the ownership structure of domestic and foreign as well as a tendency towards concentrated ownership structure manipulation of financial reporting information. La Porta, et al. (2006) explains that the strong or weak investor protection associated with the legal order that is followed by the country concerned. Indonesia and countries in Asia in general character is the structure of corporate ownership is concentrated, so the problem of differences in the primary interest is the divergence of interests between the controlling owner of the company with the majority as a minority owner.The sample of this study is a company listed on the Stock Exchange period from 2004 to 2010. Elections were conducted with a purposive sample. The structure of ownership in this study were measured with the first proxy largest percentage ownership of public companies by domestic and foreign institutions, in this study are referred to foreign institutions are foreign companies operating in Indonesia. Each ownership group is divided into majority and minority ownership group. Discretionary accruals (DTAC) is calculated with a modified Jones model (Dechow, et al., 1995). The results of this study is that there are differences in discretionary accruals of companies owned by domestic institutions and companies owned by foreign institutions. There are differences in discretionary accrual of the largest property company that first ï£ 50% and the first largest holdings ï³ 50%. Thus the results of this study have implications that in order to protect the rights of minorities, the regulators limit the percentage of single ownership of the largest first, so that ownership of minorities are protected.KeyWord: Ownership Structure, Earnings Management